Noise induced hearing loss in low frequencies in employees in a hospital microbiology department - Chrysouli, Konstantina; Kikidis, Dimitrios (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Noise induced hearing loss (NIHL) is regarded as a serious problem and one of the most recorded occupational disorders in Europe and in the rest of the world and amounts to between 7% and 21% of the hearing loss. Aim of this study is to explore the development and the prevalence of low frequency noise-induced hearing loss (NIHL) in a hospital, especially in microbiology laboratory workers. Generally it is known that 4 KHz is the main NIHL frequency. Despite current theories, our study suggests for the first time the impact of low frequency noise in hearing loss among laboratory workers. According to the results, the population examined, namely the employees at the Microbiology Department of the Hospital, showed lower hearing levels compared to the control group, who had no history of occupational exposure to noise. There are many other studies which suggest that prolonged exposures to high noise levels have negative physiological and psychological effects on workers. The finding of the correlation of noise frequency with the frequency of the generated hearing loss is involved in the controversy about the pathophysiology of noise effect.